Effects of subthalamic nucleus stimulation on motor cortex plasticity in Parkinson disease - Kim, Sang Jin (Neurology, 2015)
OBJECTIVE: We hypothesized that subthalamic nucleus (STN) deep brain stimulation (DBS) will improve long-term potentiation (LTP)-like plasticity in motor cortex in Parkinson disease (PD). METHODS: We studied 8 patients with PD treated with STN-DBS and 9 age-matched healthy controls. Patients with PD were studied in 4 sessions in medication (Med) OFF/stimulator (Stim) OFF, Med-OFF/Stim-ON, Med-ON/Stim-OFF, and Med-ON/Stim-ON states in random order. Motor evoked potential amplitude and cortical silent period duration were measured at baseline before paired associated stimulation (PAS) and at 3 different time intervals (T0, T30, T60) up to 60 minutes after PAS in the abductor pollicis brevis and abductor digiti minimi muscles. RESULTS: Motor evoked potential size significantly increased after PAS in controls (+67.7% of baseline at T30) and in patients in the Med-ON/Stim-ON condition (+55.8% of baseline at T30), but not in patients in the Med-OFF/Stim-OFF (−0.4% of baseline at T30), Med-OFF/Stim-ON (+10.3% of baseline at T30), and Med-ON/Stim-OFF conditions (+17.3% of baseline at T30). Cortical silent period duration increased after PAS in controls but not in patients in all test conditions. CONCLUSIONS: Our findings suggest that STN-DBS together with dopaminergic medications restore LTP-like plasticity in motor cortex in PD. Restoration of cortical plasticity may be one of the mechanisms of how STN-DBS produces clinical benefit.